The impact of economic recession on the health of migrant fathers over time: results from the Growing up in Ireland longitudinal study - Nazmy Villarroel; Anne MacFarlane; Maria Roura; Alphonse Basogomba; Colette Bradley; Joseph W. LeMaster; Ailish Hannigan (BMC, 2022)
Abstract Background The relationship between economic conditions and health can depend on both the health outcome measured and the composition of the population. Analysis of outcomes by both ethnicity and country of birth has been recommended. The aim of our study is to explore the impact of recession on self-rated health and depression of migrant fathers in Ireland over time, considering both ethnicity and country of birth. Methods Longitudinal data from waves of a population-representative cohort study (Growing up in Ireland, 2008-2013) was used with Wave 1 collected before the recession and Wave 2 collecting information on how the recession affected families. Socio-demographic variables, self-rated health and depression were compared across three groups of fathers classified by self-identified ethnicity and country of birth: White Irish (n = 5628), Other White European (EU-10) (n = 431), and Black African (n = 192) using chi-square tests and logistic regression models. Rates of follow-up were compared across groups at Wave 3. Results Prior to the recession, the rate of employment was lowest for African fathers (51% vs 81% for EU-10 fathers and 92% for Irish fathers, p < 0.001). At Wave 2, African families were more likely to have experienced a very significant effect of the recession (40.1% compared to 22.4% for families from EU-10 and 21.3% for Irish families, p < 0.001). However, the impact of the recession on depression and self-rated health was only found in Irish fathers. By Wave 3, rates of follow-up were lower for migrant fathers, particularly for EU-10 fathers. Conclusions Understanding the relationship between economic conditions and health is complex and may be related to multiple dimensions of socio-economic advantage and disadvantage. African families were already more likely to be disadvantaged prior to the recession and that pattern persisted during the recession. Further research on attrition rates of migrants in population cohort studies is needed and the development of effective strategies for recruitment, follow-up and analysis.